CLOUD ACCOUNTING DAN DISRUPSI PEKERJAAN AKUNTAN - Pitria, Ni Gusti Ayu; Mahyuni, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Cloud technology has entered various fields, including accounting. Cloud technology implemented in the accounting field is called cloud accounting. Implementation of cloud technology might disrupt the role of accountants in the future. The purpose of this study is to determine the extent to which cloud accounting can disrupt the work of accountants. This research was conducted using a qualitative approach with a systematic review from hundreds of journals to assist in making research study maps. The results obtained in this study include: 1. The impact of cloud accounting on the work of accountants consisting of disruptive innovation, creative innovation and sustaining innovation; 2. Strategy for accountant to face disruption. From the results of the analysis, it can be concluded that the presence of cloud accounting, robotics and data analytics (big data) through artificial intelligence (AI) can take over the basic work carried out by accountants. This requires an accountant to equip themselves with information technology capabilities to stay relevant.